2008
DOI: 10.1007/s11695-007-9379-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hemodynamic Monitoring During Laparoscopic Gastric Bypass in Superobese Patients by Pressure Recording Analytical Method

Abstract: As assessed by PRAM, this study showed no deterioration in hemodynamic indices or ventricular performance during laparoscopic gastric bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…We do not concur with Dr. Bernstein's review [1]; PRAM may be useful to assess cardiovascular changes in obese patients during laparoscopy [2], but we believe also that every monitoring application that uses a calculated parameter should be seen in its trend rather than single value.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…We do not concur with Dr. Bernstein's review [1]; PRAM may be useful to assess cardiovascular changes in obese patients during laparoscopy [2], but we believe also that every monitoring application that uses a calculated parameter should be seen in its trend rather than single value.…”
mentioning
confidence: 74%
“…It is important to discuss the data presented in the review, considering that caution is necessary to accept his conclusion on pressure recording analytical method (PRAM) [2]. We wonder how it is possible to draw similar conclusions based on the small number of studies considered and patients enrolled [3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, normalization by their respective BSAs (2.64 m 2 for Balderi et al [6] vs 2.41 m 2 for Dumont et al) produces a SI difference of 21%, which represents an unacceptable negative bias. It can therefore be stated that SI obtained by the PRAM method substantially underestimated the SI estimate found by TDCO.…”
mentioning
confidence: 96%
“…Thus, the authors ought to have stated that, for a beat-to-beat method measuring SV, comparing measurements of absolute SV and CO between different methods and patient populations is misleading. The authors must have known this to be correct because Balderi et al [6], the subject of the commentary and reply, reported their results as SI and CI ( As evidence that their values for SI and CI index are consistent with the literature, they cite studies using alternative methodology, including transesophageal echocardiography (TEE) [7] transesophageal echo-Doppler velocimetry [8] and impedance cardiography (ICG) [9,10]. Indeed, using TEE and transesophageal echo-Doppler techniques, values similar to those obtained by PRAM are reported [7,8].…”
mentioning
confidence: 99%